Analysis of angiogenesis biomarkers for ramucirumab efficacy in patients with metastatic colorectal cancer from RAISE, a global, randomized, double-blind, phase III study - Tabernero, J (Ann Oncol, 2018)
BACKGROUND: The phase III RAISE trial (NCT01183780) demonstrated that the vascular endothelial growth factor (VEGF) receptor (VEGFR)-2 binding monoclonal antibody ramucirumab plus 5-fluororuracil, leucovorin, and irinotecan (FOLFIRI) significantly improved overall survival (OS) and progression-free survival (PFS) compared with placebo + FOLFIRI as second-line metastatic colorectal cancer (mCRC) treatment. To identify patients who benefit the most from VEGFR-2 blockade, the RAISE trial design included a prospective and comprehensive biomarker program that assessed the association of biomarkers with ramucirumab efficacy outcomes. PATIENTS AND METHODS: Plasma and tumor tissue collection was mandatory. Overall, 1072 patients were randomized 1 : 1 to the addition of ramucirumab or placebo to FOLFIRI chemotherapy. Patients were then randomized 1 : 2, for the biomarker program, to marker exploratory (ME) and marker confirmatory (MC) groups. Analyses were carried out using exploratory assays to assess the correlations of baseline marker levels [VEGF-C, VEGF-D, sVEGFR-1, sVEGFR-2, sVEGFR-3 (plasma), and VEGFR-2 (tumor tissue)] with clinical outcomes. Cox regression analyses were carried out for each candidate biomarker with stratification factor adjustment. RESULTS: Biomarker results were available from >80% (n = 894) of patients. Analysis of the ME subset determined a VEGF-D level of 115 pg/ml was appropriate for high/low subgroup analyses. Evaluation of the combined ME + MC populations found that the median OS in the ramucirumab + FOLFIRI arm compared with placebo + FOLFIRI showed an improvement of 2.4 months in the high VEGF-D subgroup [13.9 months (95% CI 12.5–15.6) versus 11.5 months (95% CI 10.1–12.4), respectively], and a decrease of 0.5 month in the low VEGF-D subgroup [12.6 months (95% CI 10.7–14.0) versus 13.1 months (95% CI 11.8–17.0), respectively]. PFS results were consistent with OS. No trends were evident with the other antiangiogenic candidate biomarkers. CONCLUSIONS: The RAISE biomarker program identified VEGF-D as a potential predictive biomarker for ramucirumab efficacy in second-line mCRC. Development of an assay appropriate for testing in clinical practice is currently ongoing. CLINICAL TRIALS REGISTRATION: NCT01183780.